The humanistic and existential approach to improve students’ emotional intelligence in school counseling program - Fahlevi, Reza (Konselor, 2020)
Emotional Intelligence is highly necessary aspect that covers studentsâ€™ ability to use their emotion effectively in the learning process. Good Emotional Intelligence provides the students with appropriate ability which can help them take the best decision for their future. The lack of Emotional Intelligence often makes students feel stressed and depressed. It leads the students to destructive behaviors such as uncontrolable anger, lack of decision-making ability, and despair. Therefore, the students need to be trained to recognize, control, and develop their Emotional Intelligence in a positive way. This research is a library research, which is done by searching, reading, studying, and analyzing the content of related books and various supporting literature. Based on the research, it is concluded that school plays an important role to provide a professional counselor who can help the students improve their Emotional Intellligence effectively. The counselor is expected to have various approaches in developing student Emotional Intellegence, one of which is Humanistic and Existential Approach. This approach covers essential concepts the students have as human beings, such as what they are meant to be and what potentials they have. Through this approach, a school counselor can help students understand more about managing and controlling emotion in a positive way. Â